Błogosławiony arcybiskup Radzim-Gaudenty i zagadnienie początków metropolii gnieźnieńskiej w historiografii staropolskiej - Prokop, Krzysztof R. (Archiwa, Biblioteki i Muzea Kościelne, 2020)
Archbishop Radzim-Gaudenty, half-brother of St. Adalbert, was the first Metropolitan of the Diocese of Gniezno. Little is known about his life and work, even the date of his death is uncertain. This lack of information is connected with scarce historical sources. In this article the author reviewed the Old Polish historical sources which reveal the information about Archbishop Radzim-Gaudenty. The oldest Polish chronicles, among others, Gallus Anonymus or Wincenty Kadłubek, are silent on the matter of this hierarch. Only in the 15th century Jan Długosz in his works published a lot of information about him. In the 16th century the following authors wrote about the Metropolitan: Maciej Karpiga from Miechów, Marcin Kromer, Stanisław Orzechowski, Jan Herburt, Maciej Stryjkowski, Marcin Bielski, Piotr Skarga, Bartosz Paprocki. In the 17th century the history of the Archbishop was presented by Szymon Staropolski, Szymon Okolski, Stanisław Łubieński, Stefan Damalewicz, Piotr Hiacynt Pruszcz, Stanisław Sczygielski vel Szczygielski, Andrzej Olszowski and Stanisław Bużeński. In the 18th century the issues connected with the life of the Bishop can be found in the works of Jerzy Schwengl, Florian Jacek Jaroszewicz, Franciszek Rzepnicki, Kasper Niesiecki, Gotfryd Lengnich and Adam Naruszewicz.